PENYELESAIAN KONFLIK INTERNAL PARTAI DEMOKRAT TAHUN 2021 DENGAN CARA NON LIGITASI - Fachri Rahmad Aulia (JURNAL TRIAS POLITIKA, 2023)
ABSTRACTPolitical parties are one of the main pillars of a country that adheres to a democratic system. Therefore, political parties are required to always apply the principles of democracy in every agenda. When there is an internal conflict within the party, the political party should resolve the conflict using a democratic settlement method. The researcher will discuss the description of the resolution of the Democrat Party's internal dualism conflict that occurred between the Agus Harimurti Yudhoyono (AHY) camp and the Moeldoko camp. This study uses qualitative methods with data collection techniques based on literature studies. The theory used in analyzing the conflict resolution of the Democratic Party is through a non-litigation approach in the form of arbitration, mediation, negotiation, conciliation and asking for expert assistance. The results of this study indicate that the resolution of the Democratic Party's internal conflict can be done by: First, through arbitration, the AHY Democrats and Moeldoko's camps filed a registration request for arbitration to the Secretariat of the Arbitration Institution. Second, through negotiations, the AHY Democratic Party and Moeldoko's camps opened a dialogue to discuss the conflict and jointly seek solutions to the problems. Third, through mediation, in resolving the dualism conflict of the Democratic Party, the mediator needed is a professional who is neutral. Fourth, through conciliation, choose a conciliator who has good knowledge regarding the issue of political party conflicts. Finally, by asking for expert assistance, experts will conduct an investigation based on comprehensive considerations.ABSTRAKPartai politik merupakan pilar utama dari negara yang menganut sistem demokrasi. Maka karena itu partai politik dituntut untuk selalu menerapkan prinsip-prinsip demokrasi dalam setiap agendanya. Pada saat terjadinya konflik internal di dalam partai, partai politik seharusnya menyelesaikan konflik dengan menggunakan cara penyelesaian yang demokratis. Peneliti akan membahas gambaran penyelesaian konflik internal dualisme Partai Demokrat yang terjadi antara Kubu Agus Harimurti Yudhoyono (AHY) dengan Kubu Moeldoko. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data berdasarkan studi literatur. Teori yang digunakan dalam menganalisis penyelesaian konflik Partai Demokrat ini melalui pendekatan non-ligitasi berupa arbitse, mediasi, negosiasi, konsiliasi dan meminta bantuan ahli. Hasil penelitian ini menunjukkan penyelesainan konflik internal Partai Demokrat dapat dilakukan dengan cara: Pertama melalui abitrase, Kubu Demokrat AHY dan Kubu Moeldoko mengajukan pendaftaran untuk memohon arbitrase kepada Sekretariat Lembaga Arbitrase. Kedua melalui negosiasi, Kubu Partai Demokrat AHY dan Kubu Moeldoko membuka dialog untuk membicarakan perihal konflik dan bersama mencari solusi dari permasalahannya. Ketiga melalui mediasi, dalam menyelesaikan konflik dualisme Partai Demokrat mediator yang dibutuhkan adalah seseorang profesional bersikap netral. Keempat melalui konsiliasi, memilih seorang konsiliator yang mempunyai pengetahuan mumpuni terkait persoalan konflik partai politik. Terakhir dengan meminta bantuan ahli, nantinya para ahli akan melakukan penyelidikan berdasarkan pertimbangan komprehensif.